Unveiling the impact of COVID-19 on diabetics: vaccination status and infection rates in a North Indian state-insights from a primary healthcare centre-based non-communicable disease registry - Debnath, Aninda; Nath, Ravindra; Mondal, Anubhav; Yadav, Geeta; Lukhmana, Shveta; Kishore, Jugal (International Journal Of Community Medicine And Public Health, 2024)
Background: Patients with diabetes are at an increased risk of severe infection and mortality due to COVID-19. Absence of effective pharmacological treatments, vaccination remains one of the most effective means of controlling the pandemic. Our study aims to investigate the prevalence of COVID-19 infection among patients with diabetes mellitus and assess the coverage of COVID-19 vaccination among these patients. Methods: The patients were identified from a primary healthcare centre (PHC) based non-communicable disease (NCD) registry at PHC Najafgarh, New Delhi. A total of 480 patients were included in this study. The data was retrieved from NCD registry and vaccination status was confirmed from their vaccination certificates. Results: In our study 91.3% (438) of diabetic patients had received the first dose of COVID-19 vaccine and the coverage for second dose and third dose among these same patients are 84.6% and 27.3% respectively. Conclusions: Only a quarter of all the patients have received precautionary dose (3rd dose), and almost a tenth of all the patients have not even received a single dose of COVID-19 vaccine, the patients should be counselled and encouraged for vaccination. Also, it is recommended to take COVID-19 vaccination into consideration while taking the medical history of diabetics.